Maria Do Mar Castro Verala, Nikita Dhawan, and Antke Engel, eds. Hegemony and Heteronormativity: Revisiting “The Political” in Queer Politics. Farnham, Burlington, VT: Ashgate, 2011. 224 pp. - Richards, Stuart (Archīum Ateneo, 2013)
Excerpt: Maria do Mar Castro Varela, Nikita Dhawan and Antke Engel’s Hegemony and Heteronormativity presents a very complex analysis of “the political” in queer politics. From the outset, the editors define the object of study, “wherein ‘the political’ does not denote the sphere of politics, but the processes, regimes or logics of language, knowledge and power inherent in doing politics” (1; their emphasis). The collection of essays expands and creates a dialogue between two significant categories of queer politics: hegemony and heteronormativity. Indeed, it is the aim of this collection to rethink queer theory in terms of these concepts, “so as to avoid narrowing queer politics to a critique of normative heterosexuality and the rigid gender binary” (2). Hegemony and Heteronormativity marks out the definition of hegemony from Antonio Gramsci to Ernesto Laclau and Chantal Mouffee.